REM desensitization as a new therapeutic method for post-traumatic stress disorder: a randomized controlled trial - Ahmadi, Khodabakhsh; Hazrati, Majid; Ahmadizadeh, Mohammadjavad; Noohi, Sima (Acta medica Indonesiana, 2015)
to evaluate potential efficacy of a new therapeutic approach in posttraumatic stress disorder in comparison with eye movement desensitization and reprocessing (EMDR), a standard treatment approach and controls. the study was designed using a randomized controlled trial methodology. Participants were recruited from military servicemen aged between 25 to 50 years who were admitting hospitals of Bushehr, Iran, with the final diagnosis of PTSD. Finally 33 male patients were devided into three subgroups: G1: EMDR; G2: REM Desensitization; and group 3: controls who received no therapy. Mississippi Scale for Posttraumatic Stress Disorder, Pittsburgh Sleep Quality Index (PSQI) and a 37 item death anxiety questionnaire were used for measures. multiple comparisons showed that intrusive thoughts were significantly more likely to improve with REM Desensitization versus EMDR (P=0.03), while depression was more responsive to EMDR (p=0.03). Among the Pittsburgh scale for the quality of sleep items, sleep quality (p=0.02), sleep duration (p=0.001), and total sleep quality score (p=0.002) were significantly more likely to improve in the REM Desensitization group. Change in the absolute death anxiety scores was not different between subgroups excepting EMDR versus control group (p=0.05). REM, desensitization, the new therapeutic approach to PTSD is a highly effective strategy, even more than EMDR, the standard treatment, in most of the evaluated subjects, with special emphasis on sleep symptoms, and also in the management of intrusive thoughts. Depression is the only factor in which, REM Desensitization was significantly less likely to represent a superior therapeutic effect than EMDR.